The blog of war [Web journalism]. - Cherry, S.M.
The paper considers how Webloggers are changing the way news journalism works. It discusses the emergence of war-oriented weblogs-so called warblogs-developed by journalists and by at times obsessive civilians.
Keywords: Internet; Web journalism; Web page; Webloggers; News journalism; War-oriented weblogs; Warblogs